Effects of PETTLEP imagery technique on precision skills: a study on drag flick in Pakistan hockey - Hashmi, S.; Akhtar, T.; Hashmi, M. (Journal of Imagery Research in Sport and Physical Activity, 2020)
Present study was aimed at investigating therole of Physical, Environmental, Task, Timing, Learning, Emotion and Perspective (PETTLEP) Imagery technique inthe improvement of skill precision level of hockey dragflickers. For this purpose, both male (83) and female (38)hockey drag flickers (n=121) of age ranged between 17 and27 years were selected from different hockey teams belonging to clubs, colleges, universities, departments,regional and national academies of Pakistan. Participants were made to undergo a Pretest-Intervention-Posttest research design consisted of 20 dragflicks and filling of SIAQ questionnaire. Drag Flick Precision MeasurementTest (DFPMT) along with Sports Imagery Ability Questionnaire (SIAQ) were used to measure their skill precision levels and their imagery ability. The participants were classified into three categories as per their skill precision levels (Point-based), ranging from 48 Novice (upto12 points), 42 Intermediate (13-18 points) and 31 Elite (19 points and above), and were randomly assigned to one of four intervention groups; Physical Practice (PP), PETTLEP Imagery Practice (IP), Physical Practice+PETTLEP Imagery Practice Combination (CP), and No Practice (NP) Controlgroup. Each group performed their respective tasks for10 weeks through specially designed physical training programs aided by Imagery scripts. Paired sample t test analysis showed that all groups improved significantly (p<0.05) from pre- to post-test, and the CP group improved more with average improvement value of 8.32 for DFPMT and 5.39 for SIAQ (p<0.05) than the IP, PP and NP groups. However, there was no significant difference found between the PP (Sig. 0.73) and NP (Sig. 0.44) groups in SIAQ. Result extend prior research findings and suggests that ETTLEP Imagery practice used in combination with Physical practice has substantial impact on improving performance of complex motor skills, Present findings showed that PETTLEP imagery model was found to improve player`s precision skill levels, especially when itwas combined with physical practice. However, further studies in this connection are needed.